Metodologi penyelidikan dalam pendidikan: amalan dan analisis kajian. By Ghazali Darusalam & Sufean Hussin. Kuala Lumpur: Penerbit Universiti Malaya, 2019, pp. 630. ISBN: 978-967-488-009- 5. - Jamil, Khairil Husaini (IIUM Press, 2020)
Offering a review for the third print of a second edition of a book has proven to be a daunting task. Whilst considering the fact that the book must have achieved a certain level of reception to have justified the new print, I have to also admit at this very early instance that my area of concentration does not relate directly to the subject of the book.Nevertheless, the book under review deserves to be consulted anddiscussed by the intellectual community, particularly in departments where teacher training and research on education are showcased amongst its main agenda.